TECHNOLOGY FOR PREPARING FUTURE PRESCHOOL TEACHERS FOR PROFESSIONAL ACTIVITY BASED ON A COMPETENCY-BASED APPROACH (World Bulletin of Education and Learning, 2025)
The modernization of teacher education requires the development of effective pedagogical technologies that ensure the readiness of future preschool teachers for professional activity in rapidly changing educational contexts. A competency-based approach has become a key methodological foundation for teacher preparation, as it focuses on the formation of integrated professional competencies rather than the accumulation of fragmented knowledge. This article examines the technology for preparing future preschool teachers for professional activity based on a competency-based approach. The study emphasizes the importance of aligning educational content, teaching methods, and assessment practices with the professional competencies required in preschool education. Particular attention is given to the role of practice-oriented learning, reflective activities, and interactive pedagogical methods in developing professional readiness. The article argues that a competency-based technology in teacher education contributes to the formation of pedagogical, communicative, and reflective competencies essential for effective preschool teaching. The findings highlight that systematic implementation of competency-based training technologies enhances the quality of professional preparation and supports the development of flexible, competent, and socially responsible preschool teachers.
Keywords: competency-based approach, preschool teacher education, professional competence, pedagogical technology, teacher preparation